2014
DOI: 10.3390/ijms150610116
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AhR in Autoimmune Regulation and Its Potential as a Therapeutic Target against CD4 T Cell Mediated Inflammatory Disorder

Abstract: AhR has recently emerged as a critical physiological regulator of immune responses affecting both innate and adaptive systems. Since the AhR signaling pathway represents an important link between environmental stimulators and immune-mediated inflammatory disorder, it has become the object of great interest among researchers recently. The current review discusses new insights into the mechanisms of action of a select group of inflammatory autoimmune diseases and the ligand-activated AhR signaling pathway. Repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 75 publications
1
21
0
1
Order By: Relevance
“…In addition to the AHR mediating immunotoxic effects, it has also been identified as part of a molecular pathway of physiological immune responses, and thus as a target for immunomodulatory therapies [reviewed in (Zhu, et al 2014)]. Disease models in which AHR modulation has been suggested as a possible target include, for instance, cancer, Crohn's disease, ulcerative colitis, diabetes, MS and inflammatory skin conditions such as atopic dermatitis (Benson and Shepherd 2011, Díaz-Díaz, et al 2016, Furumatsu, et al 2011, Haas, et al 2016, Jin, et al 2014, Kerkvliet, et al 2009, Quintana, et al 2010, Singh, et al 2007, Van Den Bogaard, et al 2013 .…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to the AHR mediating immunotoxic effects, it has also been identified as part of a molecular pathway of physiological immune responses, and thus as a target for immunomodulatory therapies [reviewed in (Zhu, et al 2014)]. Disease models in which AHR modulation has been suggested as a possible target include, for instance, cancer, Crohn's disease, ulcerative colitis, diabetes, MS and inflammatory skin conditions such as atopic dermatitis (Benson and Shepherd 2011, Díaz-Díaz, et al 2016, Furumatsu, et al 2011, Haas, et al 2016, Jin, et al 2014, Kerkvliet, et al 2009, Quintana, et al 2010, Singh, et al 2007, Van Den Bogaard, et al 2013 .…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…However, some of the biological impacts of TCDD are such that they could be potentially beneficial in the treatment of certain diseases, if they could be separated from the toxicity. These impacts are particularly related to immunomodulation (Zhu, et al 2014). Appropriate activation of AHR, devoid of TCDD-like toxicity, could thus lead to novel therapeutics for treatment of, for instance, cancer, multiple sclerosis (MS), inflammatory skin diseases, Crohn's disease and colitis (Arsenescu, et al 2011, Benson and Shepherd 2011, Díaz-Díaz, et al 2016, Furumatsu, et al 2011, Haas, et al 2016, Jin, et al 2014, Quintana, et al 2008, Van Den Bogaard, et al 2013.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although the mechanisms associated with this phenomena are not clear, some families exhibit a high frequency of pituitary adenomas, and more recently, the presence of familial prolactinoma was associated with genes, such as the aryl hydrocarbon receptor interacting protein (AIP) gene, 15 which in turn is related to inflammatory conditions. 16 These data advocate for the key role of genetics in the development of pituitary adenomas, and the association between PRL and PolyA based on genetic background. Treatment effects with dopamine agonists are wide and variable.…”
Section: Discussionmentioning
confidence: 99%
“…They did not investigate the caspase-1 expression, one of the major mediator for IL-1β production in infection diseases. [ 17 ] On the other hand, several study[ 11 19 ] have shown that activation of AhR suppress production of pro-inflammatory cytokines and has a major role in autoimmune diseases. However, they did not compare the levels of expression of caspase-1 in lymphocytes, which may have caused the discrepancy between our and their results.…”
Section: Discussionmentioning
confidence: 99%